Be Agile Or Be Gone? A Three-Way Interaction Of Goal Congruence And Knowledge Sharing - Imanirrahma Salsabil; Mariah Rabiatul Qibtiyah (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2023)
Background – Digital startups in Indonesia are starting to face decline within the last 2 years, faced by rapid technological changes and fierce competition, leading some of these startups to carried out employee layoff. Aim – This study aims to identify and explore the drivers of employee agility in digital startups in Indonesia through the influence of intellectual capital. It also considers the moderating role of knowledge sharing and goal congruence. Design /Methodology /Approach – With quantitative analysis, this study chooses 250 digital startups employees as respondents, determined using purposive sampling method. The data is obtained through survey with online questionnaire, and is analyzed using conditional process analysis with SPSS Macro-PROCESS. Findings – Intellectual capital positively influences employee agility, and this influence is strengthened by the existence of knowledge sharing and goal congruence between employees in the digital startups. Conclusion – The importance of intellectual capital as a strategic asset for organizations operating in dynamic and competitive environments, while highlighting some of the conditional factors underlying the relationship. In addition, the moderating role of knowledge sharing and goal congruence has provided new insights into this relationship. Research implication – This study has implications for both academia and industry, emphasizing the significance of investing in and managing intellectual capital to foster a more agile workforce in this rapidly evolving sector. Limitations – The present study is carried out within the specific context of digital startups in Indonesia with its own characteristics, thus the finding might not be able to be generalized to other settings.